Effects of pressure on thermal contact resistance for rough mating surfaces - M. Z. Abdullah,; Y. C. Yau,; Z. A. Zainal Alauddin, and; K. N. Seetharamu (Universitas Gadjah Mada, 2001)
Thermal contact resistance has been studied experimentally to investigate the effect of pressure between two aluminium or two brass rough surfaces at three different heat flux levels. Three different rough surfaces are considered in the range of 2.63 to 40.69?m. It is demonstrated that the thermal contact resistance reduces significantly with pressure for both materials, the harder material gives higher thermal contact resistance as expected